Analisis Taksonomi Bloom dalam Pelatihan Penulisan Artikel Ilmiah dengan Penerapan Design Thinking - Fitriani, Fitriani; Nurdiyanto, Nurdiyanto; Nur’aeni, Nur’aeni; Mintarsih, Mimin (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
The challenge of master students is very tough in facing their readiness to publish course assignment articles in scientific journals. This study aims to analyze the application of design thinking in scientific article writing training, especially the research background. By using a qualitative approach, research The challenges of master students are very severe in facing their readiness to publish course assignment articles in scientific journals. This study aims to analyze the application of design thinking in scientific article writing training, especially the research background, and borrowing Bloom's Taxonomy theory as a formal object in analyzing the results of the implementation of research background writing training as the material object. A total of 21 master's degree students were involved in the training by applying this design thinking. The results and discussion of this study showed that participants were able to evaluate the results of the exercise based on the prototype of writing the background of the research, although in doing the creation it was necessary to test it on an ongoing basis. This study concludes that design thinking is relevant applied in training to design prototypes research background in writing scientific articles according to Bloom's Taxonomy theory. Several limitations and recommendations were put forward for the follow-up application of design thinking in developing optimal skills in writing articles and scientific publications.